EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) DENGAN PENDEKATAN SAINTIFIK DISERTAI DENGAN STRATEGI PETA KONSEP PADA MATERI BILANGAN DITINJAU DARI GAYA BELAJAR SISWA KELAS VII SMP NEGERI SE-KOTA METRO TAHUN PELAJARAN 2014/2015 - Priyandani, Wihasti Imas; Budiyono, Budiyono; Subanti, Sri (Jurnal Pembelajaran Matematika, 2015)
Abstract: This research aimed to know: (1) which one of the learning models gave a better achievement between TPS concept maps, TPS, or clasical, (2) which one of the students with types of learning style had a better achievement between students with visual, auditory, or kinesthetic, (3) at each learning style types, which one of the learning models gave a better achievement between TPS concept maps, TPS, or clasical, (4) at each the learning models, which one of the students with types of learning style had a better achievement between students with visual, auditory, or kinesthetic. The population of the research was the eighth class students of Junior High School at Metro regency on academic year 2013/2014 and the sample was students from SMP Negeri 2 Metro, SMP Negeri 6 Metro and SMP Negeri 5 Metro which was taken by using stratified cluster random sampling technique. This was a quasi-experimental research with a 3x3 factorial design. The data analysis technique used was unbalanced two ways analysis of variance. Based on the data analysis, it was concluded as follows. 1) TPS concept maps gave the same achievement as TPS and clasical, 2) The students with auditory had better achievement than the students with visual and kinesthetic, the students with visual gave the same achievement as students with kinesthetic, 3) In TPS concept maps, the students with visual gave the same achievement as students with auditory, the students with visual gave the same achievement as students with kinesthetic, and the students with auditory had better achievement than the students with kinesthetic. In TPS, the students with auditory had better achievement than the students with visual, the students with auditory had better achievement than the students with kinesthetic, the students with visual had better achievement than the students with kinesthetic. In clasical model, the students with visual had the same achievement as the students with auditory and kinesthetic. 4) At the students with visual, auditory, and kinesthetic. TPS concept maps gave the same achievement as TPS and clasical.Keywords: TPS concept maps, TPS, Learning Style,Â